Running with mindfulness dynamic running therapy (DRT) to improve low-mood, anxiety, stress, and depression - Pullen, William (New York, New York Plume, 2017)
Letting your mind wander as you take a long walk, a slow jog, or a brisk run can give you a powerful, uplifting feeling. Some call it a runners high, others attribute it to endorphins. In this interactive workbook, psychotherapist William Pullen teaches you how to channel that exhilarating energy and use it to make positive change in your life. This radical new approach to obtaining the benefits of mindfulness originates in the body itself. Using a combination of mindfulness, focused questions, and exercise, Dynamic Running Therapy (DRT) has proven to be a simple, intuitive, effective, and therapeutic method for managing stress, trauma, anxiety, anger, depression, and other conditions. With carefully tailored thought exercises to be implemented while on a run or walk, DRT brings the mind into perfect harmony with the body through the healing experience of mindful running.-- Back cover
The journey -- The healing environment -- Depression and low mood -- Anxiety -- Relationships -- Anger -- Decision making -- Parents and kids -- Mindful running -- Running backward -- The end of the rainbow.
Keywords: Exercise therapy; Running -- Psychological aspects; Depression, Mental -- Exercise therapy; Anxiety -- Exercise therapy; Stress (Psychology) -- Exercise therapy